Pengaruh Kerja Sama Tim, Pemberdayaan dan Pelatihan Terhadap Kinerja Karyawan - Muh. Saifuddin; Rr. Hawik Ervina Indiworo; Ika Indriasari (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The problem in this research is that employee performance decreases based on service production lead time and income targets that are not achieved from the specified targets. And the aim of this research is to analyze the influence of teamwork, empowerment and training on employee performance at PT. Nasmoco Kaligawe. The population of this research is all employees of PT. Nasmoco Kaligawe with a total of 110 employees. The sampling technique used is a saturated sampling technique, namely making the entire population into the sample. The type of data used is primary and secondary data using questionnaire and literature study data collection methods. The analytical methods used are validity testing, reliability testing, classical assumption testing, multiple linear regression testing and hypothesis testing. The results obtained in this research are: teamwork has a significant influence on employee performance in a positive direction, meaning that if teamwork gets better, employee performance will increase. Empowerment has a significant influence on employee performance in a positive direction, meaning that if empowerment is implemented appropriately, employee performance will increase. Training has a significant influence on employee performance in a positive direction, meaning that if the training provided is better and more interesting for employees, then employee performance will increase. The Adjusted R Square value is 0.797, which shows that the influence of the variables teamwork, empowerment and training on the performance of PT Nasmoco Kaligawe employees is 79.7%. Meanwhile, the remaining 20.3% is influenced by other variables that were not observed in this research.